An online checklist of banana cultivars - Crichton, R.; Vezina, A.; Bergh, Inge van den (International Society for Horticultural Science, 2016)
Banana cultivars have been given a multitude of names which is a reflection of both their morphological diversity and of the socio-linguistic diversity of the people naming them in numerous local languages around the world. The many names for banana cultivars, including synonyms and homonyms, in combination with further difficulties in cultivar description and classification means that we cannot accurately quantify such important details as how many cultivars there are and where they are distributed. We have created the Online Checklist of Banana Cultivars on the ProMusa website to bring the large amount of existing information on banana cultivar names and related relevant information into one easily accessible and searchable resource (http://www.promusa.org/Banana+cultivar+checklist). As of August 8, 2014 the Online Checklist of Banana Cultivars contains 6965 entries, with 4911 unique local names, corresponding to 1940 cultivars, in 39 subgroups, in 15 groups, in 93 locations, with the information being sourced from 38 references. We hope that the checklist will be a valuable resource for the banana community and that it will stimulate efforts to resolve outstanding issues related to the description, nomenclature and classification of the banana cultivars, including arriving at an internationally accepted name for each cultivar and elucidating a well-defined classification system.